Northwest History. Alaska, Glaciers. United States. (1937)
Glacier May Cut Alaska Highway: Awakened By Earthquake Ice Mass Less Than Mile From Road. GLACIER MAY CUT ALASKA HIGHWAY: Awakened By Earthquake Ice Mass Less Than Mile From Road FAIRBANKS, Alaska, Feb. 12 — (/P)—Alaska's speediest glaicer, shaking the earth as it moved forward, cut to less than a mile today the distance separating it from the territory's main highway and a hostelry. Aroused by an earthquake from the slumber of centuries, Black Rapids Glacier, 125 miles south of here, threatened to gouge out the Richardson highway on a two-mile front and crush the Black Rapids roadhouse, occupied by a family of three. Otto Geist, curator of the University of Alaska here, who flew to the glacier, predicted it would be only a matter of a few days before the ice mass reached the road, if the present rate of advance continues. The glacier moved a half mile yesterday. Since the earthquake the 30-mile long ice stream has advanced five miles in two weeks. Gigantic blocks of ice have continually tumbled from the glacier's 200-foot high face. The impact shakes the earth and thunderous sounds boom among the crags of the Alaska range. Timbers in the roadhouse, where Mr. raid Mrs. H. E. Revell and their son Harry, have waited apprehensively, quivered and rattled. Buckling in the glacier's middle increased, Geist said after flying ever it with Pilot Jack Herman. Geist estimated the ice was piled up for 1,000 feet at the hump, with grotesque formations developing. Black Rapids had been known as a "dying" glacier and the ice had receded from year to year, until it awakened this winter.